2010
DOI: 10.1086/653656
|View full text |Cite
|
Sign up to set email alerts
|

Evaluative Conditioning Procedures and the Resilience of Conditioned Brand Attitudes

Abstract: Changing brand attitudes by pairing a brand with affectively laden stimuli such as celebrity endorsers or pleasant pictures is called evaluative conditioning. We show that this attitude change can occur in two ways, depending on how brands and affective stimuli are presented. Attitude change can result from establishing a memory link between brand and affective stimulus (indirect attitude change) or from direct "affect transfer" from affective stimulus to brand (direct attitude change). Direct attitude change … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
224
1
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 188 publications
(246 citation statements)
references
References 46 publications
8
224
1
5
Order By: Relevance
“…Counter to our initial speculation, we found no evidence for the hypothesis that extinction depends on specific features of CS-US pairings. Although this does not exclude the possibility that extinction effects depend on other procedural factors, the generality of the obtained results is important, because the procedural factors included in the current studies have been shown to impact other functional properties of EC, such as their dependence on recollective memory (e.g., Hütter & Sweldens, 2012) and susceptibility to US revaluation (e.g., Sweldens et al, 2010). In the current studies, extinction did not depend on whether EC effects were due to simultaneous versus sequential pairings or pairings with single versus multiple USs.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Counter to our initial speculation, we found no evidence for the hypothesis that extinction depends on specific features of CS-US pairings. Although this does not exclude the possibility that extinction effects depend on other procedural factors, the generality of the obtained results is important, because the procedural factors included in the current studies have been shown to impact other functional properties of EC, such as their dependence on recollective memory (e.g., Hütter & Sweldens, 2012) and susceptibility to US revaluation (e.g., Sweldens et al, 2010). In the current studies, extinction did not depend on whether EC effects were due to simultaneous versus sequential pairings or pairings with single versus multiple USs.…”
Section: Discussionmentioning
confidence: 87%
“…In line with this contention, it has been argued that the functional properties of ECsuch as its resistance to extinction-may depend on various procedural aspects of how a CS is paired with a US (e.g., De Houwer, 2007;Gast, Gawronski, & De Houwer, 2012). For example, whereas EC effects resulting from pairings with a single US have been shown to be reversed as a result of subsequent changes in the valence of the US, EC effects resulting from pairings with multiple USs of the same valence seem to be unaffected by US revaluation (Sweldens, Van Osselaer, & Janiszewski, 2010; see also Walther, Gawronski, Blank, & Langer, 2009). Moreover, research by Hütter and Sweldens (2012) suggests that, whereas EC effects resulting from simultaneous CS-US pairings can occur without recollective memory for these pairings, EC effects resulting from sequential pairings seem to require recollective memory.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, when participants were instructed to adopt a cognitive focus, EC effects emerged only on the implicit, but not on the explicit measure. Similarly, recent research has shown that US-revaluation influences liking of a CS only when the CS was paired with a single US, but not when it was paired with multiple USs (Sweldens, Van Osselaer, & Janiszewski, 2010). These results suggest that EC is sometimes based on stimulus-stimulus learning and sometimes on stimulus-response learning (see also Gast & INTRODUCTION 14 for future theorizing is to explain why EC effects are moderated in the observed manner and to generate novel predictions that could be used to test the proposed explanations.…”
Section: Theoretic Developmentsmentioning
confidence: 87%
“…We recommend researchers interested in studying awareness to consult the original publications for more in-depth discussion of the different criteria. Here we will exemplify these criteria by considering the use of funneled debriefing protocols, one of the most frequently used methods to assess awareness of a priming procedure (e.g., Chartrand et al 2008;Dalton and Huang 2014;Fitzsimons, Chartrand, and Fitzsimons 2008;Laran, Janiszewski, and Salerno 2016;Sweldens, van Osselaer, and Janiszewski 2010;Tuk et al 2009;Wheeler and Berger 2007). Typically, a series of questions of increasing specificity is presented, ranging, for example, from "please guess the real purpose of the study," over "did you see a connection between the first and second part of this session," to "did you see a connection between the words in the first task?…”
Section: Operationalization Via Measurement: Four Criteria For Measurmentioning
confidence: 99%